2008
DOI: 10.1259/bjr/01948454
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks from diagnostic radiology

Abstract: In recent years, there has been a rapid increase in the number of CT scans performed, both in the US and the UK, which has fuelled concern about the long-term consequences of these exposures, particularly in terms of cancer induction. Statistics from the US and the UK indicate a 20-fold and 12-fold increase, respectively, in CT usage over the past two decades, with per caput CT usage in the US being about five times that in the UK. In both countries, most of the collective dose from diagnostic radiology comes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
511
1
26

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 794 publications
(540 citation statements)
references
References 111 publications
2
511
1
26
Order By: Relevance
“…Mastrangelo et al [12] suggested that orthopaedic surgeons in a hospital with poor radiation protection had a substantially greater incidence of cancer. The concern regarding the effects of radiation exposure has led to the use of ALARA (as low as reasonably achievable) techniques with healthcare workers [7]. According to the National Council on Radiation Protection and Standards, the recommended maximum annual dose of radiation to the whole body is 5000 mR and 50,000 mR to the extremities [20].…”
Section: Introductionmentioning
confidence: 99%
“…Mastrangelo et al [12] suggested that orthopaedic surgeons in a hospital with poor radiation protection had a substantially greater incidence of cancer. The concern regarding the effects of radiation exposure has led to the use of ALARA (as low as reasonably achievable) techniques with healthcare workers [7]. According to the National Council on Radiation Protection and Standards, the recommended maximum annual dose of radiation to the whole body is 5000 mR and 50,000 mR to the extremities [20].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Variability could also be explained by factors beyond the probability of injury that affect the balance of risks and benefits for a specific patient. For example, recent studies have highlighted the increased risk of harm for younger patients from ionizing radiation used in CT. 14,15 We did not find effect modification by age on the relationship between estimated probability and decisions, but physicians did underestimate the risk of pathology in children less than 1 year. This underestimation of risk likely reflects the difficulty inherent in assessing infants.…”
Section: Discussionmentioning
confidence: 52%
“…Although many radiology publications indicate that cancer risks from CT scans are extremely small, this is unfortunately not always the case [4,11,23,32,[35][36][37][38][39][40][41][42].…”
Section: Medical Worldmentioning
confidence: 99%
“…There is, however, growing evidence that earlier assumptions that CT scanning causes cancer, lack final absolute proof [16][17][18][19][20]63]. Almost all evidence is based on regression models from data from exposure to extremely high radiation dose from the Hiroshima atomic bomb [25,32,35,38,57]. These models assume and claim that there is no threshold for radiation toxicity and that even the tiniest radiation dose from a CT scan has some toxicity.…”
Section: Patientsmentioning
confidence: 99%